2022
DOI: 10.48550/arxiv.2208.06911
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Repulsive vector interaction as a trigger for the non-conformal peak in $V_s^2$

Abstract: Considering the NJL model with a repulsive vector channel, parametrized by GV , I show that one may generate a non-monotonic behavior for the speed of sound which peaks at V 2 s > 1/3. This can be achieved by assuming GV to be density dependent so that the resulting EoS is stiff/repulsive at low densities and soft/non-repulsive at high densities. The interpolation between the two regimes happens through a cross-over which takes place after the first order chiral transition sets in. The model explicitly shows t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Figure 8 shows the different magneticfield profiles as a function of baryon chemical potential, In order not to repeat all our EOS results here with the magnetic-field profiles, we show instead the EOS derivatives, namely the speed of sound squared c 2 s ¼ dP=dϵ. This quantity has been shown to be directly relevant for astrophysical discussions of, for instance, stellar masses, radii, and tidal deformability [88][89][90][91][92][93], and the outcome of binary neutron-star mergers [94][95][96]. Besides, it has been suggested that this quantity may give some information about a possible deconfinement phase transition [89].…”
Section: A Cmf Modelmentioning
confidence: 99%
“…Figure 8 shows the different magneticfield profiles as a function of baryon chemical potential, In order not to repeat all our EOS results here with the magnetic-field profiles, we show instead the EOS derivatives, namely the speed of sound squared c 2 s ¼ dP=dϵ. This quantity has been shown to be directly relevant for astrophysical discussions of, for instance, stellar masses, radii, and tidal deformability [88][89][90][91][92][93], and the outcome of binary neutron-star mergers [94][95][96]. Besides, it has been suggested that this quantity may give some information about a possible deconfinement phase transition [89].…”
Section: A Cmf Modelmentioning
confidence: 99%